Association of food hypersensitivity in children with the risk of autism spectrum disorder: a meta-analysis - Li, Hong; Liu, Haixia; Chen, Xin; Zhang, Jian; Tong, Guanglei; Sun, Yehuan (European journal of pediatrics, 2021)
This meta-analysis was performed to clarify the association between food hypersensitivity in children and autism spectrum disorder (ASD) in detail. Relevant studies published in 8 databases before March 2020 were retrieved and screened according to established inclusion criteria. The odds ratio (OR) with the 95% confidence interval (CI) was pooled to estimate the effect. Subgroup analyses were performed in terms of publication year, study design, location, sample size, definition of food hypersensitivity, definition of ASD, and study quality score. Furthermore, we stratified studies by participant sex and age to perform a more detailed analysis. This meta-analysis included 12 published articles with 434,809 subjects. A significant association was observed between food hypersensitivity and the risk of ASD (OR = 2.792, 95% CI: 2.081–3.746). The risk of ASD among girls and subjects younger than 12 with food hypersensitivity may be greater than that among boys and those older than 12. The results of sensitivity analysis and publication bias analysis show that the association is relatively stable. Conclusion : Our results showed a positive association between food hypersensitivity and autism spectrum disorder, and girls and subjects younger than 12 may be more sensitive to this association. The role of food hypersensitivity in the onset of ASD deserves more attention. What is Known: • Food hypersensitivity is a term used to describe food allergies and food intolerance. • ASD is a group of neurodevelopmental disorders that are characterized by deficits in social interaction, repetitive or stereotypic behavior, and verbal communication disorder. • The prevalence rates of ASD and food hypersensitivity in the developed world are increasing. What is New: • In this work, we reviewed and analyzed the available data and studies and found a positive association between food hypersensitivity and ASD. • Girls and children younger than 12 may be more sensitive to have ASD than boys and children older than 12.